SWOT Analysis of Rice Plants in Nganjuk Regency - Endro Puji Astoko; Nunuk Helilusiatiningsih (Formosa Journal of Multidisciplinary Research, 2023)
The economic development of the Indonesian nation includes the fields of agriculture, services, fisheries, animal husbandry and others, this is related to the sufficient availability of food needs for all Indonesian people. The availability of food is closely related to the pattern of developing food strategic areas, good cultivation systems, good post-harvest management systems and good distribution and storage systems. Problems that can be done by farmers related to post-harvest production of food crops and horticulture in Nganjuk. The aim of the research is to conduct a study and SWOT analysis of storage of rice products in Nganjuk Regency. The research uses a descriptive method of SWOT analysis with a case study approach to the community (stakeholders). The results of the analysis In Nganjuk Regency there are 12 Village Barns spread across 10 Districts. All of the Village Granaries are Warehouses for Paddy Commodities. So the conclusions in this qualitative and quantitative descriptive study using SWOT analysis are as follows: Strength: Using internal strengths with the vision of making the most of an external opportunity. Weakness: Minimizing internal weaknesses aims to obtain available external opportunities. Opportunity: Utilizing internal strengths in the face of an external threat intensively. Threat: Minimizing internal weaknesses aimed at avoiding and overcoming external threats.